The role of organizational challenges and technical challenges on the implementation of E-government military institutions - Dahwan, Aref Abdulrazzaq Ahmed; Raju, Valliappan; Kassim, Salina (World Research Union, 2022)
This study aimed to find out the challenges and barriers to the implementation of the e-governance in the Yemeni military institutions. A comprehensive literature review was conducted to the study topic. A conceptual framework was proposed that contained two independent variables that represent the challenges, which were (organizational challenges and technical challenges). The descriptive analytical approach was used in this study; it is one of the most used methods in the study of social and human phenomena, and because it fits the phenomenon. It also examines an existing phenomenon or issue from which information can be answered to the study questions without the intervention of the researcher. For this research, the instrument used to collect data from the research sample in Yemen in regards to the implementation of E-governance. The measurement of the direct impact of the independent variables (organizational challenges and technical challenges) on the implementation of e-governance in military institutions in Yemen. Smart PLS has been used to conduct statistical analysis from the primary data. Several tests have been conducted for the collected data. The main results found that there is a negative and significant relationship between organizational challenges and the Implementation of E-Governance in the Yemeni military institutions. Also, there is a negative and significant relationship between organizational challenges and the Implementation of E-Governance in the Yemeni military institutions. It is proposed that the organizational and technical challenges for the implementation of the E-Government, it is recommended that the military institutions implement policies for the dissemination of online services to avoid that the members of the military have to move from their home, it is observed that the institutional factor is also important, this can be improved by assigning a greater economic budget to innovate in the development of E-government military institutions.